2004
DOI: 10.1074/jbc.m405476200
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of HIV-1 Genomic RNA in the gp120 Gene Determines a Recombination Hot Spot in Vivo

Abstract: By frequently rearranging large regions of the genome, genetic recombination is a major determinant in the plasticity of the human immunodeficiency virus type I (HIV-1) population. In retroviruses, recombination mostly occurs by template switching during reverse transcription. The generation of retroviral vectors provides a means to study this process after a single cycle of infection of cells in culture. Using HIV-1-derived vectors, we present here the first characterization and estimate of the strength of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 34 publications
(41 reference statements)
8
86
0
Order By: Relevance
“…One possibility in the literature is that it might assist recombination. The predicted structure is similar to a secondary structure whose role in recombination in HIV has been well studied (Galetto et al 2004). They both contain an z20-bp-long stem at the base (Fig.…”
Section: Role Of the Rna Secondary Structuresupporting
confidence: 52%
See 1 more Smart Citation
“…One possibility in the literature is that it might assist recombination. The predicted structure is similar to a secondary structure whose role in recombination in HIV has been well studied (Galetto et al 2004). They both contain an z20-bp-long stem at the base (Fig.…”
Section: Role Of the Rna Secondary Structuresupporting
confidence: 52%
“…They all have been found to play important roles in HIV transcription. In addition, it has been reported that an RNA secondary structure in the gp120 gene facilitated recombination, creating a recombination hot spot in HIV (Moumen et al 2001;Galetto et al 2004). All these studies suggest that RNA secondary structure in HIV plays important roles in the viral life cycle.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, in order for HIV-1 intersubtype recombination to occur, the RNAs of the two subtypes of viruses must be copackaged into the same virion and recombination must occur during reverse transcription. We and others (13)(14)(15)(21)(22)(23)(24)(25) have examined HIV-1 recombination with subtype B-based vectors. Although there is ample evidence among the circulating variants (1) and cell culture experiments (26,27) to indicate that intersubtype recombination could occur, very little is known about the rates and limitations of recombination between different HIV-1 subtypes.…”
mentioning
confidence: 99%
“…Since local sequence motifs have been long suspected to promote HIV recombination (Balakrishnan et al 2001;Moumen et al 2001Moumen et al , 2003Negroni and Buc 2001;Galetto et al 2004), we examine this part of the HIV genome for the presence of known motifs. One of the HIV instability elements, denoted as INS2-M6 by Schneider et al (1997), covers sites [564,609] of our master alignment (see Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Following Bernardinelli et al (1995) we express our prior belief about v in terms of a ratio of recombination probabilities p i =p j % e g i Àg j . On the basis of in vitro HIV recombination detection experiments (Moumen et al 2001;Dykes et al 2004;Galetto et al 2004) we expect that site recombination probabilities should not vary more than sevenfold or equivalently that recombination log odds should not differ by .2. Since our smoothing prior implies that …”
Section: Synchronizing Recombinant and Parental Sequencesmentioning
confidence: 99%